Research on key factors of public green space environment in Macau community based on sustainable development - Junling Zhou; Pohsun Wang; Lingfeng Xie; Yifan Wang (Journal of Experimental Nanoscience, 2023)
Nanotechnology has great theoretical and application value. Nanomaterials have the characteristics of radiation, absorption, sterilization, and adsorption. Numerous studies have shown that nanotechnology plays an important role in protecting and planning public green spaces. In recent years, with the continuous improvement of Macau’s status as an international city, the development of tourism has led to the northward shift of the centre under the "spillover effect" of the residential space in the historical city. As a typical high-density community, the Macau Peninsula has a serious shortage of public green space. This paper selects Macau’s community public green spaces as research objects, takes environmental perception as the evaluation perspective, takes the supply capacity of public green space and the degree of demand of urban residents as evaluation indicators, as well as the subjective and objective factors that affect the layout of public green space, combined with relevant theories to construct A complete set of comprehensive index system. Based on the analysis results, from the attractiveness and utilization rate of public green space, the layout of public green space, urban road traffic network, land use planning, nanotechnology materials, etc., to explore effective ways to promote the sustainable development of high-density cities in Macau.